DINAMIKA PERUBAHAN PENGGUNAAN LAHAN DI SUB DAS CIRASEA (DAS CITARUM HULU) (The Dynamics of Land Use Change in The Cirasea Sub-Watershed (Citarum Hulu Watershed)) - Davik - -; Latief Mahir Rachman; Yayat Hidayat; Iwan Ridwansyah (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2022)
ABSTRAKSub DAS Cirasea merupakan salah satu Sub DAS yang memiliki peran penting dalam pengelolaan DAS Citarum Hulu. Penurunan fungsi lahan berdampak pada sistem hidrologi DAS. Hal ini disebabkan oleh perubahan penggunaan lahan. Perubahan penggunaan lahan tersebut ditentukan melalui analisis hasil klasifikasi menggunakan dengan algoritma Maximum Likelihood Classification (MLC) pada software QGIS. Klasifikasi penggunaan lahan menggunakan Citra Landsat tahun 2009-2019. Hasil klasifikasi meliputi hutan, hutan sekunder, lahan terbangun, lahan terbuka, perkebunan, pertanian lahan kering, sawah, semak belukar dan tubuh air. Uji akurasi dengan Indeks Kappa mencapai 85,15% atau hampir sempurna. Klasifikasi penggunaan lahan yang terjadi menunjukkan perubahan luas antara tahun 2009 dan 2019. Lahan yang mengalami penurunan yaitu hutan 1.437,13 ha, sawah 1.336,21 ha, hutan sekunder 367,83 ha dan pertanian lahan kering 94,14 ha. Sedangkan lahan yang mengalami peningkatan yaitu lahan terbuka 1476,69 ha, lahan terbangun 1.056,39 ha, semak belukar 463,63 ha, perkebunan 235 ha dan tubuh air 3,07 ha.Kata Kunci: daerah aliran sungai, fungsi hidrologi, MLC, Indeks Kappa, penggunaan lahan ABSTRACTThe Cirasea sub-watershed is one of the sub-watersheds that has an important role in the management of the Upper Citarum watershed. The decline in land use has an impact on the hydrological system of the watershed, which is caused by changes in land use. The land-use change is determined by analyzing the results of the classification using the Maximum Likelihood Classification (MLC) algorithm in QGIS software. Land use classification using Landsat Image 2009-2019. The classification results include forest, secondary forest, built-up areas, open land, plantations, dryland farming, rice fields, shrubs, and water bodies. The accuracy test using the Kappa Index reached 85.15% or almost perfect. The land use classification that occurs shows changes in the area between 2009 and 2019. The land that has decreased is 1,437.13 ha of forest, 1,336.21 ha of rice fields, 367.83 ha of secondary forest, and 94,148 ha of dryland farming. Meanwhile, land that has increased is 1,476.69 ha of open land, 1,056.39 ha of built-up areas, 463.63 ha of shrubs, 235 ha of plantations, and 3.07 ha of water bodies.Keywords: watershed, hydrological function, MLC, Kappa Index, land use